Pendapat Ulama dan Empat Imam Madzhab Tentang Hukum Musik di dalam Islam - Aulia Rahmadina; Sholihul Anas Hanafi; Nurlita Ayuni; Ahmad Mu’is (Journal of Religion and Social Community | E-ISSN : 3064-0326, 2024)
The issue of music law in Islam has been a controversial topic among scholars for a long time. This study examines the views of the four major schools of thought in Islam-Imam Abu Hanifah, Imam Malik, Imam Shafi'i, and Imam Ahmad bin Hanbal-as well as other prominent scholars on the status of music from the perspective of Islamic law. Some scholars state that music is absolutely forbidden (haram) based on the arguments of the Qur'an and Hadith, while others allow it (halal) under certain conditions, especially if music does not lead to sinful acts or neglect worship. In this study, the arguments of each madhhab are presented, including the views of Imam Abu Hanifah who tends to be strict, Imam Malik who is more moderate, as well as the opinions of Imam Shafi'i and Imam Ahmad who give nuances to the prohibition with special conditions. In addition, some contemporary scholars also provide more contextualised views by considering the times and cultural developments. This research aims to provide a comprehensive understanding of the variation of opinions in Islamic law related to music, as well as how the principles of sharia are applied in various social and cultural contexts.